2020
DOI: 10.1259/bjr.20201030
|View full text |Cite
|
Sign up to set email alerts
|

Increased chemokines levels in patients with chronic obstructive pulmonary disease: correlation with quantitative computed tomography metrics

Abstract: Objective: We sought to explore the relationships between multiple chemokines with spirometry, inflammatory mediators and CT findings of emphysema, small airways disease and bronchial wall thickness. Methods: All patients with COPD (n = 65) and healthy control subjects (n = 23) underwent high-resolution CT, with image analysis determining the low attenuation area (LAA), ratio of mean lung attenuation on expiratory and inspiratory scans (E/I MLD) and bronchial wall thickness of inner perimeter of a 10-mm diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Overexpression of IL-18 in the airways in patients with COPD has been shown and can lead to emphysema, the development of fibrosis in the bronchi and blood vessels of the lungs, and the formation of pulmonary hypertension [7,8]. Due to its T-helper type 2 cell-(Th-2-) inducing functions, IL-18 can also participate in inflammation and hyperreactivity of the respiratory tract in asthma and promote the recruitment of eosinophils to the airways [9][10][11][12]. On the other hand, IL-18 would further induce immune cells to produce a large amount of inflammatory factors to aggravate the disease [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of IL-18 in the airways in patients with COPD has been shown and can lead to emphysema, the development of fibrosis in the bronchi and blood vessels of the lungs, and the formation of pulmonary hypertension [7,8]. Due to its T-helper type 2 cell-(Th-2-) inducing functions, IL-18 can also participate in inflammation and hyperreactivity of the respiratory tract in asthma and promote the recruitment of eosinophils to the airways [9][10][11][12]. On the other hand, IL-18 would further induce immune cells to produce a large amount of inflammatory factors to aggravate the disease [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that CXCL12 is significantly upregulated in the serum of COPD patients compared with that of healthy controls, and is positively correlated with small airway disease and emphysema detected using high-resolution chest CT scans. 51 When the Cxcl12/Cxcr4 signaling axis was blocked, the number of neutrophils decreased, and reverse migration increased inflammation levels. 52 The CXCL12 antagonist, AMD3100, can ameliorates emphysema-like manifestations in mice induced using cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines mediate recruitment of immune cells into inflammatory lesions, and are related to the development of COPD. 19 A previous study has demonstrated that CXCL10 could recruit CXCR3+ type-1 T-lymphocytes to the peripheral airways of smokers with COPD, and type-1 T-lymphocytes express interferon gamma to promote activation of macrophages, thus releasing inflammatory cytokines, including IL-6, IL-8, TNF-α, and IL-1β. (20) Therefore, increased serum CXCL10 was regarded as a biomarker of COPD.…”
Section: Competing Interestsmentioning
confidence: 99%